Perlindungan Hukum Bagi Anak Korban Kekerasan: Studi Normatif Terhadap Peraturan Perundang-undangan - Simanjuntak, Predderics Hockop (Universitas Medan Area, 2024)
This article discusses legal protection for child victims of violence in Indonesia, with 15,267 cases recorded in 2024 according to SIMFONI-PPA. Even though Law Number 35 of 2014 exists, challenges to law enforcement remain, such as social stigma, lack of public knowledge about children's rights, and lack of rehabilitation facilities. This study aims to analyze existing regulations and the role of society, government, and non-government organizations in improving legal protection. The findings show the importance of collaboration between government, civil society, and society to improve child protection. This research also emphasizes the need for open communication with children so that they dare to report the violence they have experienced. Overall, this research concludes the need for a comprehensive and cooperative approach to safeguarding the rights and welfare of children in Indonesia